Efek Larvasida Ekstrak Etanol Daun Sirih (Piper betle.L) terhadap Larva Aedes aegypti - Esy Maryanti; John Rico Manalu; Yolazenia Yolazenia; Suri Dwi Lesmana; Mislindawati Mislindawati (Jurnal Ilmu Kedokteran, 2022)
Betel a leaf is a medicinal plant and consists of alkaloids, saponins and eugenol. Based on the experiment done to mosquito larvae by Cheng et al. resulted the extract of betel leaf has LD50 was 33 ppm. This research aimed to determine LC50 and LC90 of ethanolic extract of betel leaf (Piper betle L.) on the larvae of Aedes aegypti. The preliminary test had done to determine 10-90% mortality. Following concentrations that used for the final test were 300 ppm, 400 ppm, 600 ppm, 800 ppm, 1000 ppm, 1200 ppm, 1400 ppm, and one negative control. LC50 value from ethanolic extract of betel leaf was 467,441 ppm and LC90 value was 869,412 ppm. Larvicides effect from betel leaf because of chemical compound which had positive allosteric modulator of GABA mechanism. In conclusion, ethanolic extract of betel leaf (Piper betle L.) is potential to develop as mosquito larvicides.